IL-17-producing γδ T cells and neutrophils conspire to promote breast cancer metastasis - Coffelt, Seth B.; Kersten, Kelly; Doornebal, Chris W.; Weiden, Jorieke; Vrijland, Kim; Hau, Cheei-Sing; Verstegen, Niels J. M.; Ciampricotti, Metamia; Hawinkels, Lukas J. A. C.; Jonkers, Jos; de Visser, Karin E. (Nature (London), 2015)
Tumours maximize their chance of metastasizing by evoking a systemic inflammatory cascade in mouse models of spontaneous breast cancer metastasis. A novel cancer metastasis pathway That tumorigenesis can be closely linked to an inflammatory microenvironment has been well established. In a new study, Karin de Visser and colleagues estimate the more systemic inflammatory effects observed in a mouse model of breast cancer. They find that interleukin (IL)-1β expression in tumours elicits IL-17 expression in γδ T cells at a local level, which through granulocyte colony-stimulating factor production promotes systemic accumulation of neutrophils in multiple organs. Interfering with this cascade of events, for example at the level of neutrophil activation, reduces lung and lymph node metastases in this breast cancer model. These findings illustrate the perhaps wider than anticipated systemic effects elicited by localized tumours, at the same time offering multiple points of potential therapeutic interference. Metastatic disease remains the primary cause of death for patients with breast cancer. The different steps of the metastatic cascade rely on reciprocal interactions between cancer cells and their microenvironment. Within this local microenvironment and in distant organs, immune cells and their mediators are known to facilitate metastasis formation 1 , 2 . However, the precise contribution of tumour-induced systemic inflammation to metastasis and the mechanisms regulating systemic inflammation are poorly understood. Here we show that tumours maximize their chance of metastasizing by evoking a systemic inflammatory cascade in mouse models of spontaneous breast cancer metastasis. We mechanistically demonstrate that interleukin (IL)-1β elicits IL-17 expression from gamma delta (γδ) T cells, resulting in systemic, granulocyte colony-stimulating factor (G-CSF)-dependent expansion and polarization of neutrophils in mice bearing mammary tumours. Tumour-induced neutrophils acquire the ability to suppress cytotoxic T lymphocytes carrying the CD8 antigen, which limit the establishment of metastases. Neutralization of IL-17 or G-CSF and absence of γδ T cells prevents neutrophil accumulation and downregulates the T-cell-suppressive phenotype of neutrophils. Moreover, the absence of γδ T cells or neutrophils profoundly reduces pulmonary and lymph node metastases without influencing primary tumour progression. Our data indicate that targeting this novel cancer-cell-initiated domino effect within the immune system—the γδ T cell/IL-17/neutrophil axis—represents a new strategy to inhibit metastatic disease.